UV/VISIBLE spectra of selected natural photoprotective flavanoids: a density functional theory study - Juine Arvie J. Lavarias. 4 0 16; 5 (2022)
u
Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2022.
Keywords: 2 -- 0; 6; 20; 20; 2